2014
DOI: 10.1007/s10722-014-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genetic diversity in 23 early Polish oat cultivars based on molecular and morphological studies

Abstract: In Poland oat breeding began at the late nineteenth century. During the World War II almost all of Polish breeding materials were lost, and then were replaced by German cultivars. The main aim of this paper was to show the level of genetic diversity of Polish oat cultivars which were bred before 1939. Simultaneously usefulness and informativeness of molecular and morphological methods were tested and compared. This study involved 23 cultivars, which were described by 25 morphological traits and three types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…The difference could result from lower number of cultivars from an earlier period which have survived till today. Analogous results were obtained during the evaluation of morphological differentiation of these materials (Boczkowska et al 2014). The values of diversity coefficients clearly indicated that the old cultivars were undoubtedly formed by breeding programs, but criteria were not as stringent as those used in modern breeding.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The difference could result from lower number of cultivars from an earlier period which have survived till today. Analogous results were obtained during the evaluation of morphological differentiation of these materials (Boczkowska et al 2014). The values of diversity coefficients clearly indicated that the old cultivars were undoubtedly formed by breeding programs, but criteria were not as stringent as those used in modern breeding.…”
Section: Discussionsupporting
confidence: 55%
“…1) and, what is more important, they represented completely different phenotypes. Plants belonging to Koscielecki cultivar had white lemma colour, equilateral type of panicle while Grzywacz Póxny Wolymski had yellow colour of lemma and unilateral panicle (Boczkowska et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of genetic diversity can assist in reliable classification of collections required for crop improvement (Mohammadi and Prasanna 2003;Manohar and Murthy 2012). Morphological analysis has been used for characterizing large data sets and such description has become a valuable source of information for agronomic and breeding programs (Boczkowska et al 2014). In the present study, the morphological classification of 36 accessions revealed a great diversity in fruit morphological traits across India.…”
Section: Discussionmentioning
confidence: 68%
“…In general, the DC lines have lower variation than the STH pool. Interestingly, that similar analyses performed on 23 old cultivars using AFLP, ISSR and RAPD markers failed in any significant grouping of the analysed materials (Boczkowska et al, 2014). The data demonstrates that the analysed materials show enough variation useful for breeding purposes.…”
Section: Discussionmentioning
confidence: 51%